2019
DOI: 10.1109/tnsm.2019.2950158
|View full text |Cite
|
Sign up to set email alerts
|

Reliable BIER With Peer Caching

Abstract: BIER (Bit-Indexed Explicit Replication) alleviates the operational complexities of multicast protocols (associated to the multicast tree and the incurred state in intermediate routers), by allowing for source-driven, per-packet destination selection, efficient encoding thereof in packet headers, and stateless forwarding along shortest-path multicast trees. BIER perpacket destination selection enables efficient reliable multicast delivery: packets not received by a subset of intended destinations can be efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…is paper focuses on the theoretical and experimental study of stability in distributed, decentralized systems for resource discovery and allocation in non-deterministic, heterogenous, time-variant networking and communication infrastructures. is analysis can be relevant for a number of use cases: multicast content distribution in data centers [1] or in other constrained infrastructures, distributed applications and systems including information-centric architectures [2], mechanisms for dynamic allocation of workloads in the cloud [3], computing resources in data centers [4] or in other deployments of the Internet edge [5]. In all these systems, the study of performance is challenging as these systems increasingly rely on distributed multi-party architectures, involving uncoordinated or loosely coordinated agents that interact to each other, may have partial, possibly inconsistent views of the environment, and follow autonomous, possibly con icting policies.…”
Section: Problem Statementmentioning
confidence: 99%
“…is paper focuses on the theoretical and experimental study of stability in distributed, decentralized systems for resource discovery and allocation in non-deterministic, heterogenous, time-variant networking and communication infrastructures. is analysis can be relevant for a number of use cases: multicast content distribution in data centers [1] or in other constrained infrastructures, distributed applications and systems including information-centric architectures [2], mechanisms for dynamic allocation of workloads in the cloud [3], computing resources in data centers [4] or in other deployments of the Internet edge [5]. In all these systems, the study of performance is challenging as these systems increasingly rely on distributed multi-party architectures, involving uncoordinated or loosely coordinated agents that interact to each other, may have partial, possibly inconsistent views of the environment, and follow autonomous, possibly con icting policies.…”
Section: Problem Statementmentioning
confidence: 99%
“…However, it relies on source to retransmit the recovery packets. To solve this problem, the reliable BIER mechanism was extended to support recovery from peers in [31]. Rather than being directly sent to the source, NACKs can be first transmitted through an ordered set of peers, each of which may provide retransmission if they have a cached copy of the lost packet.…”
Section: Reliable Multicast In Ip and Icnmentioning
confidence: 99%
“…ICN enables rapid data retrieval due to its native in-network caching mechanism, thus shares properties with cache-based reliable multicast protocols, by enabling data recovery from nearby routers [31]. In [44], the authors found that using ICN in-network packet-level cache for retransmission can reduce the expected retransmission latency and is a valuable error control method.…”
Section: Cache Strategy In Reliable Multicastmentioning
confidence: 99%
“…This solution completely relies therefore on the unicast routing to forward multicast packets to the destination nodes. Since its first appearance, BIER attracted much attention for its simplicity, and works have been presented to enhance its basic functionality, for instance, with reliable multicast transmission [31], packet caching for fast retransmission [32], and fast reroute in case of failure [33].…”
Section: Brief Overview Of Multicast Routing In the Internetmentioning
confidence: 99%